A tandem journey through the labyrinth - Marcia B Baxter Magolda (Association for Learning Development in Higher Education (ALDinHE), 2010)
Good company is beneficial on any journey, particularly in complex journeys. Higher education is a complex journey in which learners refine their purpose, establish a vision for their lives, question long-held assumptions, and construct more complex ways of making meaning of knowledge, themselves, and their relations with others. To be good company, educators must balance providing appropriate guidance with empowering learners to direct their own learning journeys. I have used a tandem bicycle metaphor to describe the learning partnerships that help learners move toward self-authoring their beliefs, values, identities and social relations (Baxter Magolda, 2001, 2009). Educators take the back seat of the bicycle to fulfill the stoker role - to help provide the pedaling power needed to propel the bicycle forward. Learners take the front captain's seat to direct the journey. Learners and educators share authority and expertise in this mutual journey such that the learner is able to achieve the interdependence required to succeed in adult life.